Difficulties in diagnosing infectious diseases in children in outpatient settings - E. V. Barakina; D. O. Ivanov; V. A. Reznik; M. V. Red’kina; V. N. Timchenko; T. M. Chernova; V. F. Suhoveckaja; T. A. Kaplina; O. V. Bulina (Журнал инфектологии)
Infectious diseases occupy a leading place in the pathology of children and adolescents, accounting for 70–80% of the structure of morbidity and causes of mortality. Underestimation of clinical manifestations of infectious diseases by pediatricians is the reason that this pathology is not diagnosed in time, which leads to inadequate therapy, worsening of the course and chronicity of the process.Purpose of the study. Assess the nature of the pathology and the reasons for referring children by district pediatricians for consultation with an infectious disease specialist at the consultative and diagnostic center (CDC).Materials and methods. A retrospective analysis of the medical records of 532 children aged 0-17 years who sought specialized medical care from an infectious disease specialist at the Clinical Diagnostic Center of the St. Petersburg State Pediatric Medical University of the Ministry of Health of the Russian Federation in 2021-2023 was conducted.Results and discussions. The most frequent diagnoses for referral to an infectious disease specialist were: «frequently ill child» (31.0%), «prolonged cough» (20.7%), «streptococcal infection» (15.6%), «infectious mononucleosis» (13.7%), «salmonellosis, prolonged excretion of salmonella» (10.2%), «congenital herpesvirus infection» (8.8%). The immediate reasons for seeking specialized medical care were identified: insufficient clinical effect from the therapy performed in outpatient settings (36.3%); lack of eradication of the infectious pathogen from the child’s body (25.8%): the need for in-depth laboratory and instrumental examination (24.2%), the desire of parents to receive specialized medical care in an expert-level institution (13.7%).Conclusion. In outpatient settings, pediatricians have difficulties in diagnosing patients with infectious pathology, which is due to insufficient alertness to various childhood infections and the lack of opportunity for in-depth laboratory and instrumental examination.In addition, to establish a final diagnosis, a multidisciplinary approach is often required with the participation of doctors of various specialties (otolaryngologist, allergist, neurologist, audiologist, etc.).